2008
DOI: 10.1111/j.1365-2982.2008.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and gestation‐dependent pattern of corticotrophin‐releasing factor receptor subtypes in ovine fetal distal colon

Abstract: Meconium passage is frequently observed in association with feto-maternal stress factors such as hypoxia and infection, but the triggering mechanism is unknown. We hypothesize that differential regulation of corticotrophin-releasing factor (CRF) receptors during gestation play an important role in determining the susceptibilities of the fetus to stress-induced in utero meconium passage at term. We examined the innervation patterns of CRF-receptor type 1 (CRF-R1), a stimulator of gastrointestinal motility and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
4
6
0
Order By: Relevance
“…One paper describes the expression of CRF1 in the distal colon of the ovine fetus, where it was expressed in muscle tissue, enteric ganglia, and goblet cells. Generally CRF1 immunoreactivity is seen to increase during gestation, especially in the enteric ganglia (Lakshmanan et al, 2008). Muramatsu et al (2000) showed CRF1 mRNA expression in human lamina propria mononuclear cells.…”
Section: Expression Of Crf-related Peptides In the Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…One paper describes the expression of CRF1 in the distal colon of the ovine fetus, where it was expressed in muscle tissue, enteric ganglia, and goblet cells. Generally CRF1 immunoreactivity is seen to increase during gestation, especially in the enteric ganglia (Lakshmanan et al, 2008). Muramatsu et al (2000) showed CRF1 mRNA expression in human lamina propria mononuclear cells.…”
Section: Expression Of Crf-related Peptides In the Colonmentioning
confidence: 99%
“…Another study did not report any CRF2 expression in the enteric plexuses of guinea pig (Bisschops et al, 2006). Finally, expression of CRF2, just like that of CRF1, was investigated in the ovine fetus: CRF2 expression in muscle layers was found to decrease with gestation, while neuronal expression was limited to fibers of unspecified origin (Lakshmanan et al, 2008). An overview of the colonic expression of CRF-related peptides is provided in Figure 3.…”
Section: Expression Of Crf-related Peptides In the Colonmentioning
confidence: 99%
“…CRFR1 is found in the enteric nervous system and the mucosal layer 14,19 of the gut and a recent report provided evidence that activation of these peripheral receptors could stimulate an increase in colonic motility, defecation, permeability and visceral pain sensation 17 . By contrast, activation of peripheral CRFR2, which has been detected in the mucosa, 14 mucosal inflammatory cells 20 and in enteric neurons, 21,22 induces inhibition of gastric emptying, suppresses stimulated colonic motor function and prevents the hypersensitivity to repeated colorectal distension (CRD) 23–25 . Furthermore, CRFR2 has been proposed to have a role in stress‐induced permeability dysfunction and the modulation of mucosal immune and inflammatory responses in the colon 26–28 …”
mentioning
confidence: 99%
“…32 Our findings can be summarized as follows: CRF-R1-and CRF-R2-specific antibodies strongly immunostained longitudinal and circular smooth muscles in addition to muscularis mucosa in colonic segments at all gestational ages. A marked decrease in CRF-R2 immunostaining occurred in smooth muscle layers close to term.…”
Section: Crf Systemmentioning
confidence: 58%